KASMARAN "Health Cadre of Cardiovascular and Hypertension" with the Implementation of Health Promotion Model in Management Hypertension: KASMARAN “Kader Sehat Jantung dan Sigap Hipertensi” dengan Penerapan Health Promotion Model dalam Pengendalian Hipertensi - Mareta Dea Rosaline; Diah Tika Anggraeni; Nayla Kamilia Fithri; Fiora Ladesvita; Zhafira zhafarina; Tasya (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Hypertension and heart disease are global health problems increasing morbidity in Indonesia. The partner problems that were resolved were related to strengthening and optimizing cadres in helping the government related to hypertension problems in the community. Management of hypertension is considered complex because blood pressure tends to be unstable. The purpose is to optimize the empowerment of cadres, Health Cadre of Cardiovascular and Hypertension (KASMARAN), with the application of the Health Promotion Model in the prevention and control of hypertension. KASMARAN was formed with the concept of, by, and for people with hypertension, meaning that trained cadres can quickly educate the public. The location is in Grogol Village, Depok City, West Java. The result is an increase in knowledge of cadres based on the pre-test and post-test results, as much as 93%. Health education is expected to create a healthy community so that it can increase knowledge, attitudes, and awareness to be able to prevent and control hypertension and heart disease